Cephalgic Syndrome Correction in Pedia - Аndrey P. Rachin; Larisa L. Korsunskaya; Maria A. Zavadskaya; Tatyana F. Golubova; Olga I. Garmach; Aleksandr V. Zavadskiy; Lyudmila A. Pisanaya (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. Diagnosis and treatment of headache in pediatric patients is of priority medical and social importance, including when correcting it at the sanatorium and health resort stage. Difficulties and problems are associated with the complexity of taking an anamnesis in children, incorrect diagnosis, comorbidity, the need for timely correction of risk factors, and the appointment of the effective pathogenetically proved treatment. AIM. To determine the structure and features of the cephalgic syndrome in pediatric patients undergoing treatment in Evpatoria sanatoriums and to determine the effectiveness of psychological correction in the treatment of patients with frequent tension-type headache by using the method of music therapy method. MATERIAL AND METHODS. As a result of a complex examination of pediatric patients, 150 patients with headache complaints were selected out of 513 examined by the method of simple random sampling. Together with a psychologist, a subgroup of 30 patients with frequent tension headaches was selected from the total number of patients after psychological testing for whom music therapy was included in the treatment plan. RESULTS AND DISCUSSION. In the structure of the cephalgic syndrome the prevalence of tension headache was revealed, while 20% of patients had frequent episodic tension headache against the background of increased anxiety and fatigability, which significantly affects quality of life and social functioning. The patients who underwent correction of tension headaches by music therapy showed improvement of extraversion indices, reduction of neuroticism, decrease of anxiety, fatigability and irritability indices, decrease of frequencyand intensity of headaches. None of the patients were diagnosed with headache according to ICHD-III in the referral diagnosis for sanatorium treatment, but were diagnosed with vegetative-vascular dystonia and other comorbidities. CONCLUSION. The obtained data of a complex examination made it possible to substantiate a pathogenetically differentiated rehabilitation course in sanatorium treatment and led to an increase in the efficiency and quality of treatment for each patient. Using the method of music therapy, emotional and psychological correction was carried out, which occupies an important place in the relief of headache in pediatric patients.